1980
DOI: 10.1021/jm00178a020
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of 11-(1-piperazinyl)-5H-pyrrolo[2,1-c][1,4]benzodiazepine as central nervous system agents

Abstract: Four 11-(1-piperazinyl)-5H-pyrrolo[2,1-c][1,4]benzodiazepines were prepared and evaluated as central nervous system agents. All were active psychotropic agents as determined by animal screening tests. The most interesting compound, 11-(1-piperazinyl)-5H-pyrrolo[2,1-c][1,4]benzodiazepine, showed dual activity as an antidepressant against tetrabenazine depression and as a neuroleptic as measured by protection vs. amphetamine lethality in grouped mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…To couple the biaryl units with the benzopyrrolodiazepine moiety, the methyl ester functionality was hydrolyzed and converted to its acid chloride. Subsequent reaction with 10,11-dihydro-5 H -pyrrolo­[2,1- c ]­[1,4]­benzodiazepine, 8 , synthesized according to reported procedures, provided the desired biaryl functionalized benzopyrrolodiazepines ( 4a – 4c ). To introduce a carboxyl group solely at the 3-position of the tricycle, aromatic acylation with trichloroacetyl chloride in the presence of Hünig’s base was performed followed by a haloform type reaction with aqueous NaOH to give the corresponding carboxylic acids ( 5a – 5c ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…To couple the biaryl units with the benzopyrrolodiazepine moiety, the methyl ester functionality was hydrolyzed and converted to its acid chloride. Subsequent reaction with 10,11-dihydro-5 H -pyrrolo­[2,1- c ]­[1,4]­benzodiazepine, 8 , synthesized according to reported procedures, provided the desired biaryl functionalized benzopyrrolodiazepines ( 4a – 4c ). To introduce a carboxyl group solely at the 3-position of the tricycle, aromatic acylation with trichloroacetyl chloride in the presence of Hünig’s base was performed followed by a haloform type reaction with aqueous NaOH to give the corresponding carboxylic acids ( 5a – 5c ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…A further study involved the conversion of 4 to 7 through the reaction of the former with CH 3 I . The resulting lactim thioether function of 7 underwent facile nucleophilic displacements with a wide variety of cyclic secondary amines to give compounds 10a , 10b , 10c , 10d , 10e , 10f , 10g , 10h . Compounds 10a , 10b , 10c , 10d , 10e , 10f , 10g , 10h were characterized on the basis of their spectral data.…”
Section: Resultsmentioning
confidence: 99%
“…(304306) In 1978, a limited clinical trial of anthramycin was conducted for reduction of anxiety(307) followed by a study two years later in mice to study the effects on the central nervous system, in particular depression. (308) Shortly thereafter, Hurley & Thurston showed that anthraymcin’s position 11 forms adducts with the exocyclic amine of guanosine residues in the dsDNA minor groove and may have sequence selectivity. (309) A detailed structure–activity relationship (SAR) study by Thurston indeed revealed sequence selectivity of PBDs for the DNA minor groove,(310) culminating in the discovery that PBDs form a covalent bond with the exocyclic amine of guanosine in the minor groove, preferring R-G-R triples (where R is A or G) and indicating that the small molecule binding site spans three base pairs.…”
Section: Small Molecules Targeting Nucleic Acid Sequencementioning
confidence: 99%